\(\sqrt{8-2\sqrt{7}}\)-\(\sqrt{8+2\sqrt{7}}\)rút gọn

">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

19 tháng 7 2019

\(\sqrt{8-2\sqrt{7}}-\sqrt{8+2\sqrt{7}}\)

\(\sqrt{7}-1-\left(1+\sqrt{7}\right)\)

\(=\sqrt{7}-1-\sqrt{7}-1\)

= -2

29 tháng 6 2018

A= \(\sqrt{8+2\sqrt{7}}+\sqrt{8-2\sqrt{7}}\)=\(\sqrt{\left(\sqrt{7}+1\right)^2}+\sqrt{\left(\sqrt{7}-1\right)^2}=\)\(1+\sqrt{7}+\sqrt{7}-1=2\sqrt{7}\)

\(B=\sqrt{9+4\sqrt{5}}+\sqrt{9-4\sqrt{5}}\)

=\(\sqrt{\left(\sqrt{5}+2\right)^2}+\sqrt{\left(\sqrt{5}-2\right)^2}=\)\(\sqrt{5}+2+\sqrt{5}-2=2\sqrt{5}\)

24 tháng 7 2020

Trả lời:

\(D=\sqrt{11-6\sqrt{2}}-3+\sqrt{2}\)

\(D=\sqrt{9-6\sqrt{2}+2}-3+\sqrt{2}\)

\(D=\sqrt{\left(3-\sqrt{2}\right)^2}-3+\sqrt{2}\)

\(D=3-\sqrt{2}-3+\sqrt{2}\)

\(D=0\)

\(E=\sqrt{23+8\sqrt{7}}-\sqrt{7}\)

\(E=\sqrt{16+8\sqrt{7}+7}-\sqrt{7}\)

\(E=\sqrt{\left(4+\sqrt{7}\right)^2}-\sqrt{7}\)

\(E=4+\sqrt{7}-\sqrt{7}\)

\(E=4\)

7 tháng 9 2019

a, \(\sqrt{8-2\sqrt{7}}-\sqrt{8+2\sqrt{7}}\)

\(=\sqrt{7-2\sqrt{7}+1}-\sqrt{7+2\sqrt{7}+1}\)

\(=\sqrt{\left(\sqrt{7}-1\right)^2}-\sqrt{\left(\sqrt{7}+1\right)^2}\)

\(=\sqrt{7}-1-\sqrt{7}-1=-2\)

b, \(\sqrt{3+2\sqrt{2}}+\sqrt{6-4\sqrt{2}}\)

\(=\sqrt{2+2\sqrt{2}+1}+\sqrt{4-2.2\sqrt{2}+2}\)

\(=\sqrt{\left(\sqrt{2}+1\right)^2}+\sqrt{\left(2-\sqrt{2}\right)^2}\)

\(=\sqrt{2}+1+2-\sqrt{2}=3\)

7 tháng 9 2019

câu 1 đã làm 

câu 2

\(\sqrt{\left(\sqrt{2}+1\right)^2}+\sqrt{\left(2-\sqrt{2}\right)^2}\)

\(\Leftrightarrow\sqrt{2}+1+\sqrt{2}-2\Leftrightarrow2\sqrt{2}-1\)

21 tháng 9 2020

\(A=\sqrt{7-2\sqrt{10}}+\sqrt{7+2\sqrt{10}}\)

\(A^2=\left(7+2\sqrt{10}+7-2\sqrt{10}\right)+2\sqrt{\left(7-2\sqrt{10}\right)\left(7+2\sqrt{10}\right)}\)

\(=14+2\sqrt{49-40}=14+6=20\)

Khi đó:\(A=\sqrt{20}\)

Các câu còn lại bạn làm nốt nhé

18 tháng 5 2019

\(A=\sqrt{4+\sqrt{7}}-\sqrt{4+\sqrt{7}}\Leftrightarrow\sqrt{2}A=\sqrt{8+2\sqrt{7}}-\sqrt{8+2\sqrt{7}}\)

\(\Leftrightarrow\sqrt{2}A=\sqrt{\sqrt{7}^2+2\sqrt{7}+1}-\sqrt{\sqrt{7}^2+2\sqrt{7}+1}\)

\(\Leftrightarrow\sqrt{2}A=\sqrt{7}+1-\sqrt{7}-1=0\)

\(\Leftrightarrow A=0\)